Working with refugee families coping with trauma and displacement in family relationships - De Haene, Lucia; Rousseau, Cécile (Cambridge University Press, 2020)
The field of refugee family research and intervention forms a growing field of scientific study, focussing on the refugee family as the central niche of coping with, and giving meaning to, trauma, cultural uprooting, and exile. This important new book develops an understanding of the role of refugee family relationships in post-trauma healing and provides an in-depth analysis of central clinical-therapeutic themes in refugee family psychosocial interventions. Expert contributions from across transcultural psychiatry, psychology, psychotherapy and social work have provided chapters on post-trauma reconstruction in refugee family relationships, trauma care for refugee families, and intersectorial psychosocial interventions with refugee families. This exploration of refugee family systems in both research and clinical practice aims to promote a systemic perspective in health and social services working with families in refugee mental health care.